LEGAL EDUCATION IN UZBEKISTAN: CURRENT STATE AND DEVELOPMENT PROSPECTS - Ziyoda Boratova (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2020)
This article discusses the state policy in the sphere of legal education of recent years and some problematic issues that exist in the field of training and retraining of legal personnel. In article also found a brief overview of a number of specific measures, listed in the Decree of the President of the Republic of Uzbekistan dated April 29, 2019 ?On additional measures to radically improve legal education and science in the Republic of Uzbekistan?, for improving the system of legal education, involving the introduction in educational process of innovative and advanced international educational standards, improving human potential and motivation of the professors, as well as strengthening material-technical base of educational institutions